2018
DOI: 10.1371/journal.ppat.1006842
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa rugose small-colony variants evade host clearance, are hyper-inflammatory, and persist in multiple host environments

Abstract: Pseudomonas aeruginosa causes devastating infections in immunocompromised individuals. Once established, P. aeruginosa infections become incredibly difficult to treat due to the development of antibiotic tolerant, aggregated communities known as biofilms. A hyper-biofilm forming clinical variant of P. aeruginosa, known as a rugose small-colony variant (RSCV), is frequently isolated from chronic infections and is correlated with poor clinical outcome. The development of these mutants during infection suggests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 76 publications
4
82
0
2
Order By: Relevance
“…Additionally, Staudinger et al (16) demonstrated that host factors associated with the CF lung environment promote bacterial aggregation, which in turn contributes to reduced killing by neutrophils and the host defense oxidants, H 2 O 2 and HOCl (15,16). Aggregation may also be associated with recurrent inflammation in chronic P. aeruginosa infections, as well as with protection from antimicrobial products (17,18,35,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Staudinger et al (16) demonstrated that host factors associated with the CF lung environment promote bacterial aggregation, which in turn contributes to reduced killing by neutrophils and the host defense oxidants, H 2 O 2 and HOCl (15,16). Aggregation may also be associated with recurrent inflammation in chronic P. aeruginosa infections, as well as with protection from antimicrobial products (17,18,35,42).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated whether the tolerance of aggregated bacteria to gentamicin was due to protection conferred by the physiology of bacteria within the aggregates. With the use of established methodology (35), the aggregates were physically disrupted by forcing them through a 22-gauge needle several times prior to antibiotic treatment. Interestingly, disruption of aggregated PAO1 WT bacteria did not substantially increase susceptibility of bacteria to gentamicin (Fig.…”
Section: P Aeruginosa (Pao1) Flagella Are Dispensable For Formation mentioning
confidence: 99%
“…In P. aeruginosa , increased c-di-GMP, among many responses, leads to overproduction of exopolysaccharides, Psl and Pel, and matrix proteins 12 , 13 . As a result, RSCVs have hyper-biofilm phenotypes 13 , 14 , increased tolerance to antimicrobials 10 , and enhanced resistance to immunity 15 , 16 . P. aeruginosa RSCVs also evolve from in vitro grown biofilms 17 , 18 , suggesting that there is strong selection for ecological diversification in both in vivo and in vitro biofilms.…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…Further analysis of DC-SIGN and MR binding to P. aeruginosa biofilms using ELISA-based assays identified binding of DC-SIGN to biofilms generated by the Psl-deficient mutant Δ wsp F Δ psl (16)(Table 1); this mutant is not expected to contain mannose-rich carbohydrates. The Δ wspF background confers constitutive high levels of cyclic-di-GMP, overproduces Psl and promotes biofilm formation; a phenotype that resembles that of small rough colony variants found during chronic infection (17). MR-CTLD4-7 displays reduced binding to Δ wsp F Δ psl biofilms indicating that the psl operon is likely responsible for the generation of MR-CTLD4-7 ligands (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%